Influence of Sheet Thickness and Process Parameters on the Microstructure and Mechanical Properties of Brazed Welding Used for Cold-Formed Steel Beams - Hulka, Iosif; Ungureanu, Viorel; Saraolu, Silviu; Popescu, Alin; Pascu, Alexandru (MDPI AG, 2025)
Metal inert gas (MIG) brazing was used to join galvanized thin sheets with thicknesses in the range of 0.8 to 2 mm in a lap joint configuration using CuAl8 wire as filler. The process was used to manufacture built-up cold-formed steel beams composed of corrugated steel webs and flanges made from thin-walled cold-formed steel lipped channel profiles. The effect of heat input and sheet thickness on joint properties, such as macro- and microstructure, wettability, and mechanical characteristics such as microhardness and tensile strength were investigated. The bead geometry was assessed by studying the wetta- bility of the filler material. The microstructure was investigated by digital and scanning electron microscopy, and the composition in the heat-affected zone (HAZ), interface, and bead was determined by energy dispersive spectroscopy. Formation of Fe–Al intermetallics was observed in the bead at the bead–base material interface. Some pores were noticed that formed due to the evaporation of the zinc coating. The bead shape and mechanical properties were found to be the best when 1.2 and 2 mm sheets were brazed using a heat input of 121.4 J/mm. This suggests that not only the heat input but also the thickness of the sheet metal play a crucial role in the production of MIG brazed joints.
Keywords: MIG; brazing; cold-formed steel beams; microstructure; mechanical properties